(untitled) (Research, Society and Development, 2022)
An organization must go beyond simply offering a product or providing a quality service to be successful (Ost & Silveira, 2018). Organizations must meet the expectations of their customers, properly manage their environmental aspects and impacts, and provide a safe and healthy work environment. In this sense, the International Organization for Standardization (ISO) has structured standards to support companies in structuring management systems focused on specific themes, such as "Quality" through the ISO 9001:2015 standard, "Environment" through the ISO 14001:2015 and “Occupational Health and Safety” through ISO 45001:2018. Many companies have chosen to integrate these systems, which characterizes the establishment of an integrated management system (IMS). In order to support organizations and professionals who want to identify the similarities between these three standards, demonstrating the feasibility of implementing an IMS, this work aims to present the main common criteria regarding to the three standards. Each of the three standards was analyzed and it was found that all they have the same number of sections and these sections have identical nomenclatures and similar guidelines. Considering the level of subsection, although there are particularities in each standard, which is justifiable considering that each one is focused on a specific theme, it is also clear that there are many structural similarities between them. Thus, it is concluded that the three standards have a similar structure, which demonstrates the feasibility of implementing an SGI in an organization.